A comparison of the accuracy of Willems' and Cameriere's methods based on panoramic radiography. (September 2019) - Ozveren, Neslihan; Serindere, Gozde; Meric, Pamir; Cameriere, Roberto
Highlights: Estimating age plays a significant role in forensic odontology. Cameriere's method provided a better percentage of accuracy than Willems' for Turkey population. Combined usage of age estimation methods may help to hinder misjudgements based on dental age. Abstract: Tooth development evaluation is majorly the current approach to identify age and maturity. Dental age (DA) is therefore considerably emphasized in forensic and pediatric dentistry. The aim of this study was to assess the applicability of Willems and Cameriere methods for Turkish children. Panoramic images of 636 Turkish healthy children (319 male; 317 female) aged between 6 and 15 years were assessed. DA of the subjects was determined by using Willems and Cameriere methods. The seven right and left permanent lower teeth were valued using these two methods. The mean chronological age (CA) of the subjects was 11.53 ± 2.25 (min:6, max:14.99) years (boys: 11.29 ± 2.34 years, girls: 11.77 ± 2.15 years). Willems method overestimated the CA (p ≤ 0.001), in contrast, Cameriere method underestimated the CA (p ≤ 0.001) for both sexes. In different age groups the mean difference between the CA and DA calculated by Cameriere method (CADA) ranged from 0.86 to −0.41 years for boys and from 1.00 to −0.21 years for girls, while the mean difference between the CA and DA calculated by Willems method ranged from −0.26 to −0.71 years for boys and from 0.19 to −0.76 years for girls. Cameriere method provided a better percentage of accuracy (84.6% and 77.3% for males and females, respectively) in the absolute difference values within 1 year compared to Willems method. Cameriere method performed slightly better but, both methods may be used for DA estimation in the Turkish population.